Fabella Fractures after Total Knee Arthroplasty with Correction of Valgus Malalignment - Thomas Christian Kwee; Ben Heggelman; Robert Gaasbeek; Maarten Nix (Case Reports in Orthopedics, 2016)
The incidence of fabella fractures is considered to be extremely low. This report presents two patients with femorotibial osteoarthritis and considerable preoperative valgus malalignment, who developed a fracture of the fabella (as demonstrated by radiography) after total knee arthroplasty with intraoperative correction of the valgus malalignment. Special attention should be paid to the fabella for not missing a fabella fracture in these patients.